2009
DOI: 10.4025/cienccuidsaude.v8i2.8195
|View full text |Cite
|
Sign up to set email alerts
|

Características das vítimas de queimaduras atendidas em unidade de emergência de um hospital escola do noroeste do Paraná

Abstract: RESUMONa categoria de morte por causas externas no Brasil figuram as queimaduras, as quais, apesar da frequência com que aparecem no cotidiano das unidades de emergência, constituem uma área de escassas estatísticas. No presente estudo, o objetivo é identificar o perfil dos indivíduos e os tipos de acidente por queimadura que são atendidos em uma unidade de pronto atendimento de um hospital escola do Noroeste do Paraná. Trata-se de um estudo descritivo e transversal com uma população de 108 queimados, atendido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
6
0
4
Order By: Relevance
“…In a study conducted in a teaching hospital in the Northwestern region of Parana, a facility known in the metropolitan region as the main choice to the provision of care to burn patients, it was found that the assessment of burns by professionals was based on two parameters: depth and location of the lesions. There was no reference to the measurement of burned body surface, information that is critical to the definition of the proper conduct and referrals (6) .…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in a teaching hospital in the Northwestern region of Parana, a facility known in the metropolitan region as the main choice to the provision of care to burn patients, it was found that the assessment of burns by professionals was based on two parameters: depth and location of the lesions. There was no reference to the measurement of burned body surface, information that is critical to the definition of the proper conduct and referrals (6) .…”
Section: Introductionmentioning
confidence: 99%
“…No que concerne aos acidentes domésticos infere-se que a maioria poderia ter sido evitado se as pessoas estivessem cientes dos riscos a que estão expostos diante de fatores como: acender churrasqueira e fogão a lenha com álcool, descuido com os líquidos quentes, uso de fogos de artifício, dentre outros. Em estudo realizado em um Hospital Escola do Noroeste do Paraná, os resultados demonstraram que os acidentes domésticos foram os mais frequentes em relação aos outros tipos de acidentes por queimaduras (21) . Resultados semelhantes foram identificados em estudo epidemiológico no qual 45,7% das queimaduras dos pacientes ocorreram no domicílio (22) .…”
Section: Discussionunclassified
“…Besides, several studies developed in Brazil, both in general hospitals and in specialized treatment centers, indicate the male sex as the most frequently reached [26]. According to Nestor A and Turra K [27], men are more affected by these diseases by working in harsh services, being more exposed to traumas and accidents.…”
Section: Discussionmentioning
confidence: 99%
“…And also the world literature places heat/fire as a first agent, followed by scalding [28]. For Balan et al [26], the thermal agent is the major cause of burns, followed by chemical and electrical agents. Scalding accidents are associated with handling hot liquids in the home environment [2].…”
Section: Discussionmentioning
confidence: 99%